Enhancement of holographic performance and stability of photopolymer materials by introducing epoxy resin and dyes. (December 2022) - Liu, Yourong; Shen, Tong; Kang, Biao; Li, Shaoxing; Zheng, Zengrong; Lv, Huaqing; Zheng, Jihong
Highlights: Developed photopolymers by introducing high-refractive-index epoxy resin and dyes. Recorded transmission grating with more than 90 % DE and high transparency at 532 nm wavelength. The dual-photoinitiator can synergistically improve the grating photosensitivity and have a low shrinkage rate. Recorded grating displayed the resistance to degradation on aging and better storage stability. Angle multiplexing and polarization holography prove the photopolymers have the ability of high-density data recording. Abstract: The use of a composite photopolymer system together with a photoinitiator have a significant effect on the optical properties of a volume phase holographic grating. This paper reports on the performance of a low refractive index monomer combined with a high refractive index epoxy resin. Performance improvements include the compatibility between the cross-linked network structure of the matrix and the recording medium. The effects of the exposure conditions and the internal composition of the materials on holographic performance were investigated. The results showed that the optimal refractive index modulation depends on the ratio of the epoxy resin and the pre-polymerization temperature. The use of Irgacure 784 as a photoinitiator gave better performance than Rose Bengal (RB) in terms of diffraction efficiency (∼92.5 %), transmittance (∼98 %) and slight shrinkage (0.314 %) was observed. The use of a dual-photoinitiator gave improvements in the radical generation rate and the stability, permitted recordings at an exposure energy of 50 mJ/cm 2 and afforded high sensitivity (3.9 × 10 -2 cm 2 /J) as a result of the synergy between the two photoinitiators. In other words, due to the highly reactive Irgacure 784 and the inhibiting polymerization characteristics of RB, enhancement of holographic performance and good stability were realized. It was shown in the photocuring and aging experiments that the photopolymer possessed anti-aging properties. The photopolymer can record multiplexed images at 532 nm and polarization holograms, demonstrating that it has the capability to perform high-density data recording.